Effect of Ginger Juice Water on Blood Glucose Levels and Histopathology of Pancreatic Beta Cells Experimental Studies on Alloxan Induced Wistar Male Rats - Djaman, Qatthrunnada; Goenarwo, Edijanti; Mashoedi, Imam (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Hyperglycemia is one of the signs of diabetes mellitus, the disease is still being suffered by the people of Indonesia. Oral antidiabetic drugs mostly give unwanted side effects, then the experts developed a system of traditional medicine for diabetes mellitus. The research aimed to determine the effect of ginger juice on blood glucose levels and histopathological of pancreatic beta cells in male wistar rats induced by alloxan.Design and methods: An experimental study with a post-test only control group design, the study subjects white male wistar rats. Rats were divided into 5 groups, each group consisted of 5 rats, the group I was the control group (no treatment), group II is diabetic group (negative control), group III is Ginger + diabetes group, diabetes group is a group IV + Ginger + glibenclamide at a dose of each half, the group is the group of diabetic + V Glibenklamid.Results: The mean blood glucose levels were highest 172.02 Â± 21.40 mg / dl is the K II. Lowest mean glucose levels were 112.72 Â± 14.49 mg / dl for KV. Score the highest rates of pancreatic beta cell damage that is at the K II, while the lowest in the K V. Conclusion: Ginger Juice effect on blood glucose levels alloxan-induced rats. Ginger juice histopathologic effect on pancreatic beta cells alloxan-induced rats (Sains Medika, 4(2):165-173).